汉语水平考试居家考试与纸笔考试和现场机考成绩比较研究 ——以印尼泗水考点为例 - Budi Kurniawan (Jurnal Asosiasi Program Studi Mandarin Indonesia (Jurnal APSMI), 2022)
摘要新冠肺炎疫情期间，汉考国际实行HSK 居家网络考试。2020 年5 月，印尼泗水HSK考点也开始举办居家考试。目前有关居家考试的研究还非常少，而考虑到居家考试的信度，需要研究居家考试的成绩，尤其是与纸笔考试成绩的比较。因为纸笔考试和现场机考得分也出现差异现象，基于三者是目前采用的考试形式，本研究对泗水考点居家考试和纸笔考试以及现场机考成绩进行比较。统计结果表示，HSK（一级）至（三级）纸笔考试和现场机考成绩基本高于居家考试。相反，HSK（四级）至（六级）居家考试成绩基本高于纸笔考试和现场机考。居家考试信度受几个因素的影响，即考试地点、考生群体、监控效力以及考试环境。关键词: HSK；HSK 居家考试；HSK 成绩；泗水考点 AbstractDuring the COVID-19 pandemic, Chinese Testing International implemented HSK HomeEdition. In May 2020, the HSK test center in Surabaya, Indonesia also began to hold homeedition tests. At present, there are very few studies on HSK Home Edition, and considering thereliability of HSK Home Edition, it is necessary to study the scores of HSK Home Edition,especially the comparison with paper-based test scores. Because the scores of thepaper-based test and the on-site computer-based test are also different, and currently thesethree forms of HSK are all used, this study compares the scores of HSK Home Edition withpaper-based and on-site computer-based HSK at the Surabaya test center. Statistics show thatthe scores of HSK (Level 1) to (Level 3) paper-based tests and on-site computer-based testsare basically higher than that of Home Edition. On the contrary, the scores of the HSK (Level4) to (Level 6) Home Edition are basically higher than those of the paper-based test and theon-site computer-based test. HSK Home Edition reliability is affected by several factors,namely testing location, participant groups, proctoring effectiveness, and testing environmentKeywords: HSK; HSK Home Edition; HSK score; Surabaya test center